2015
DOI: 10.5488/cmp.18.43703
|View full text |Cite
|
Sign up to set email alerts
|

Statistical theory of thermodynamic and dynamic properties of the RbHSO_{4} ferroelectrics

Abstract: Within the modified four-sublattice model of RbHSO 4 with taking into account the piezoelectric coupling to the strains ε i , ε 4 , ε 5 , and ε 6 , the polarization components, static and dynamic dielectric permittivity of clamped and free crystal are calculated in the mean field approximation. At the proper choice of the values of the theory parameters, a satisfactory quantitative description of the available experimental data is obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…The PE phase of KDP has a body-centered tetragonal 𝑏𝑐𝑡 structure with shorter lattice constant along the tetragonal axis. The space group is I 42d or D 12 2𝑑 . In the FE phase, the crystal is 0.8% shear distorted along the [110] direction and becomes orthorhombic with space group Fdd2 or C 19 2𝑣 .…”
Section: Shell Model and Ab Initio Methods Calculation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PE phase of KDP has a body-centered tetragonal 𝑏𝑐𝑡 structure with shorter lattice constant along the tetragonal axis. The space group is I 42d or D 12 2𝑑 . In the FE phase, the crystal is 0.8% shear distorted along the [110] direction and becomes orthorhombic with space group Fdd2 or C 19 2𝑣 .…”
Section: Shell Model and Ab Initio Methods Calculation Detailsmentioning
confidence: 99%
“…In spite of these efforts, the controversy about whether tunneling [4,5] or geometrical effects [2,3] are at the root of the giant isotope effect still remains. This phenomenology is widely observed in the whole family of H-bonded ferroelectric compounds [6][7][8][9][10][11][12][13] including organic ferroelectrics that were recently discovered which attract much attention because of their potential for ecofriendly technological applications [14,15]. Ab initio (AI) calculations have shown that tunneling and geometrical effects are involved in a self-consistent phenomenon that greatly amplifies the effect of their correlation leading to the huge isotope effect observed [7,16].…”
Section: Introductionmentioning
confidence: 96%
“…The rest of the parameters J 0 f f ′ and ∆ 0 f are determined by the crystal symmetry, as discussed in (5). The deformation potentials ψ f f ′ j and ϕ f j are: ψ111 = −1700 K, ψ112 = −4600 K, ψ113 = −500 K, ψ114 = 0 K, ψ115 = 1200 K, ψ116 = 3500 K, ψ121 = −500 K, ψ122 = −3040 K, ψ123 = −500 K, ψ124 = 0 K, ψ125 = 400 K, ψ126 /k B = −7000 K, ψff ′ j = ψ f f ′ j /k B .…”
Section: Comparison Of the Numerical Calculations With Experimental Datamentioning
confidence: 99%
“…In [4] the four-sublattice model with an asymmetric two-well potential has been proposed for the RbHSO 4 crystal, which also takes into account the piezoelectric coupling between the pseudospin and lattice subsystems. This model permitted to obtain a qualitatively correct description of the elastic constants, and a quantitatively correct description of the static and dynamic dielectric and thermal properties of this crystal; in [5] the dielectric properties of deuterated RbDSO 4 have been successfully described by the same model. The influence of hydrostatic pressure on the phase transition and longitudinal dielectric permittivity of RbHSO 4 were explored [6]; an attempt to predict the effects of the uniaxial pressures and the shear stress σ 5 on the dielectric permittivity was made in [6,7].…”
Section: Introductionmentioning
confidence: 95%
“…Later in [9], based on a four-sublattice pseudospin model of Rochelle salt [10] account also the piezoelectric coupling of the pseudospin and lattice subsystems. This model allowed us to describe qualitatively elastic constants, the dielectric and thermal properties of the crystal, as well as dielectric properties of a deuterated RbDSO 4 crystal [11]. Based on this model, we described the eect of hydrostatic pressure on the phase transition and longitudinal dielectric permittivity of the RbHSO 4 crystal [12]; also an attempt was made This work may be used under the terms of the Creative Commons Attribution 4.0 International License.…”
Section: Introductionmentioning
confidence: 99%